ВПЛИВ СХЕМНОГО РІШЕННЯ НИЗЬКОТЕМПЕРАТУРНОГО ХОЛОДИЛЬНОГО КОНТУРУ НА ОСНОВІ ЕКОЛОГІЧНО БЕЗПЕЧНИХ ХОЛОДОАГЕНТІВ НА ЕНЕРГОЕФЕКТИВНІСТЬ ЦИКЛУ - KOZIN, V.; SHARAPOV, S.; BARSUKOVA, H. (PH “Akademperiodyka”, 2026)
Introduction. Artificial cold at temperatures of –40 0C and below is widely used in various electrotechnological processes. At the same time, the choice of refrigerant and the configuration of the refrigeration cycle determine not only energy efficiency, but also the environmental safety of the system.Problem Statement. For deep-cold conditions, multi-stage or cascade circuits are typically applied, with a rational selection of refrigerant pairs to ensure high efficiency.Purpose. To assess the influence of the circuit design — given the environmental characteristics of refrigerants — on the energy efficiency of a low-temperature refrigeration cycle using the coefficient of performance (COP) and exergy efficiency (ε), and to provide practical recommendations for selecting both the circuit type and the refrigerants.Materials and Methods. A thermodynamic and exergetic comparative analysis of theoretical low-temperature refrigeration cycles has been performed. Numerical modeling has been carried out in REFPROP for specified temperatures (tc = 45 0C; tb = –45 0C). The analyzed schemes include: a two-stage vaporcompression refrigeration machine (VCRM) with an intermediate tank and coil; cascade systems for the refrigerant pairs R717/R13, R717/R23, R717/R290, R717/R744, and R717/R32; a modified cascade cycle; and a three-stage VCRM.Results. The highest energy efficiency (COP = 2.22; ε = 0.372) has been achieved using a three-stage R717 VCRM. Among conventional cascade refrigeration cycles, R717/R290 has been identified as the most energy-efficient (COP ≈ 2.00) and environmentally acceptable pair. The modifi d cascade cycle has de monstrated higher efficiency (COP ≈ 2.07) than conventional cascade schemes, and its implementation has enabled a notable reduction in thermomechanical parameters, positively affecting compressor service life.Conclusions. For low-temperature applications, multi-stage R717 VCRM systems should be preferred, as they have proven more energy-efficient than cascade circuits. When installation reliability is of primary importance, a modified cascade cycle with R717/R290 is advisable. For such a cycle, a rule for selecting the intermediate temperature has been proposed.